2006
DOI: 10.1063/1.2189192
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric effect in very thin film Pt∕Au thermocouples

Abstract: The thickness dependence of the thermoelectric power of Pt films of variable thickness on a reference Au film has been determined for the case when the Pt film thickness, t, is not large compared to the charge carrier mean free path, ℓ, that is, t / ℓ. Pt film thicknesses down to 2.2 nm were investigated. We find that ΔS F = S B -S B F (where S B B and S F are the thermopowers of the Pt bulk and film, respectively) does not vary linearly as 1/t as is the case for thin film thermocouples when the film thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…In a calibration experiment with these two types of probes, we found that the 100 nm probe produced a temperature-thermoelectricity curve that showed an almost perfect match with the standard curve produced by a regular macro-sized TC, while the readings from the 50 nm probe showed deviations from the standard curve ( Figure 1B and 1C and Supplementary information, Figure S2). This result is consistent with earlier reports that when the thickness of the Pt film decreases beyond the 100 nm range, it will affect the resulting thermoelectric power compared to the macrosized TC at the same temperature [6,7]. Thus, we have chosen the 100 nm probe in further experiments.…”
supporting
confidence: 78%
“…In a calibration experiment with these two types of probes, we found that the 100 nm probe produced a temperature-thermoelectricity curve that showed an almost perfect match with the standard curve produced by a regular macro-sized TC, while the readings from the 50 nm probe showed deviations from the standard curve ( Figure 1B and 1C and Supplementary information, Figure S2). This result is consistent with earlier reports that when the thickness of the Pt film decreases beyond the 100 nm range, it will affect the resulting thermoelectric power compared to the macrosized TC at the same temperature [6,7]. Thus, we have chosen the 100 nm probe in further experiments.…”
supporting
confidence: 78%
“…Moreover, welding technologies for low-dimensional materials have been found to be effective for manipulating materials 11 and for generating functional elements, e.g., thermoelectric 15,16 and optical elements, 17 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the relative Seebeck coefficient of thin films decreases as the film thickness is reduced to less than 200 nm [9], [10]. The impact of different metal combinations on the Seebeck coefficients of the nanowire thermocouples was characterized with the platform described in [11].…”
Section: Introductionmentioning
confidence: 99%